EFQM in vocational education – teacher and student perspectives - Maria Gianni; Efthalia Kontou; Ilias Avdikos; Eftychia Kessopoulou; Styliani Xanthopoulou (Quality Education for All)
Purpose – Stakeholder satisfaction relates closely to service quality and performance of educational organizations. Often, this relationship is addressed in literature through the lens of excellence models, such as the European Foundation for Quality Management (EFQM) model. Nevertheless, limited studies focus on the effect of the EFQM model enablers on stakeholder satisfaction and hardly any in vocational education. To fill this void, the aim of this paper is to investigate the relationship between EFQM enablers (leadership, human resources, processes) and stakeholder satisfaction under the different perspectives of teachers and students in Greek public vocational education. Design/methodology/approach – To address the research purpose, the authors used the case study methodology. The authors used mixed research methods, the focus group method and survey. Specifically, the focus group method used to distill the EFQM enablers related to the Greek context and to develop a questionnaire administered to teachers and students of a vocational education school. From September 2021 to June 2022, 90 teachers and 216 students participated in the survey. Findings – The partial least squares structural equation modeling (PLS-SEM) method was used for data analysis, indicating that leadership and human resources have a positive and significant relationship with the satisfaction of both students and teachers. However, results did not corroborate the relationship between processes and stakeholder satisfaction either from the student’s or the teacher’s perspective. Originality/value – This paper fills a gap in existing literature by exploring the impact of EFQM enablers on stakeholder satisfaction in vocational education and training (VET), from the perspectives of both teachers and students. The findings assist VET institutions in prioritizing areas for improvement and help companies to develop strategies that consider key stakeholders' needs.